Termos de responsabilidade: análise linguística e uma proposta de hipertexto - Silva, Karen Letícia Bueno da (2024)
The present work, under the theoretical framework of Historical Sociolinguistics, aims to transcribe and analyze phonological, paleographic, and graphic aspects in past records, to establish the socio-historical profile of one of the scribes of the documents and to propose a non-linear reading through Hypertexts. The research corpus comprises 22 Terms of Responsibility dated from 1854 to 1866 of the City Council of Porto Alegre/RS, with facsimile editions made by the Arquivo Histórico Moysés Vellinho and diplomatic transcriptions made by the author of this dissertation. This research was divided into nine chapters that give an account of the brief history of the formation of the state Rio Grande do Sul and the city Porto Alegre, the considerations about Historical Sociolinguistics, and Digital Humanities, the analysis of dados, the socio-historical profile of the scribe Joaquim Manoel de Azevedo Junior and pilot proposal of Hypertext in relation to the Terms of Responsibility. The results indicate that in phonological aspects there is the presence of hyper segmentations, hypo segmentation and vowel lowering from /u/ to /o/; in the paleographic aspects we saw that, due to the function performed, the scribes are considered skilled, while in the graphic questions there are occurrences of geminated, use of diacritics, improper consonant clusters and graphic variation in words. The socio-historical profile of Joaquim Manoel de Azevedo Junior revealed that he and his family were illustrious and important citizens for the city of Porto Alegre in the period. With the pilot proposal of the Hypertext, through the website it was possible to demonstrate the functionality of the Digital Humanities for access to the transcripts and information of this research. Thus, this research, therefore, is justified by helping to characterize the Portuguese of Rio Grande do Sul in the nineteenth century, relating language, society and history.